Economic Empowerment of People Through Development of Sharia Cooperatives in Rural Communities - Ulum, Bachrul; Firmansyah, Mohammad; Hasan, Zaenol; Halili, Halili (Sahwahita: Community Engagement Journal, 2024)
A strategic initiative to enhance community well-being is the establishment of sharia cooperatives in rural communities to enable economic empowerment of the populace. Community members can access fair and sustainable financing, financial services, and business opportunities through Sharia cooperatives, which adhere to Islamic economic principles. Through this agreeable, country networks can take advantage of neighborhood potential, fortify monetary organizations, and increment aggregate pay. Through the establishment of sharia-based cooperatives in rural communities, this study seeks to identify and evaluate effective strategies for enhancing the economic well-being of local communities and ensuring the long-term viability of a sharia-based economy. The purpose of this study, which was carried out at the Kalisat Jember Branch of KSPP Syariah BMT NU Jatim, is to ascertain the development of the community-based economic level as well as the community's interest in the products that are offered. This exploration was led utilizing an information assortment process utilizing perception, meetings and documentation. Editing, organizing, and analyzing are the steps that go into processing data, and case studies are used in analysis. According to the findings of this study, the establishment of sharia cooperatives in rural areas enhances people's economic well-being. Through preparing and coaching, helpful individuals can oversee funds utilizing sharia standards, increment pay and set out new business open doors. Accordingly, the social and monetary fortitude of the local area becomes more grounded.